Spelling Proficiency of Children with a Resolved Phonological Speech Sound Disorder Treated with an Integrated Approach-A Long-Term Follow-Up Randomized Controlled Trial - Denise I. Siemons-Lühring; Amélie E. Hesping; Harald A. Euler; Lars Meyer; Corinna Gietmann; Boris Suchan; Katrin Neumann (MDPI AG, 2023)
Phonological developmental speech sound disorders (pDSSD) in childhood are often associated with later difficulties in literacy acquisition. The present study is a follow-up of the randomized controlled trial (RCT) on the effectiveness of PhonoSens, a treatment for pDSSD that focuses on improving auditory self-monitoring skills and categorial perception of phoneme contrasts, which could have a positive impact on later spelling development. Our study examines the spelling abilities of 26 German-speaking children (15 girls, 11 boys; mean age 10.1 years, range 9.3-11.2 years) 3-6 years after their successful completion of the PhonoSens treatment. Spelling assessment revealed that only 3 out of 26 participants developed a spelling disorder. In the overall population of fourth-graders, one in five children showed a spelling deficit; in another study of elementary school children, with resolved pDSSD, 18 of 32 children had a spelling deficit. Thus, the applied pDSSD treatment method appears to be associated with positive spelling development. Multiple regression analysis revealed that among the potentially predictive factors for German-speaking children with resolved pDSSD to develop later spelling difficulties, parental educational level and family risk for developmental language disorder (DLD) had an impact on children's spelling abilities; gender and the child's phonological memory had not.